1)-x=-2,7
x=2,7
2)-2+x=0
x=2
3)m-8=-13
m=-13+8
m=-5
4)p-5 3/8=6,5
p-43/8=6,5
p=6,5+43/8
p=13/2 + 43/8
p=52/8 + 43/8
p=95/8
p=11 7/8
5)x+0,16=-1,24
x=-1,24-0,16
x=-1,4
6)-2-x=-0,8
-x=-0,8+2
-x=1,2
x=-1,2
7)|x-1|=3
1.x-1=-3
x=-3+1
x=-2
2.x-1=3
x=3+1
x=4
8)|x+3|=1
1.x+3=-1
x=-1-3
x=-4
2.x+3=1
x=1-3
1)-x=-2,7
x=2,7
2)-2+x=0
x=2
3)m-8=-13
m=-13+8
m=-5
4)p-5 3/8=6,5
p-43/8=6,5
p=6,5+43/8
p=13/2 + 43/8
p=52/8 + 43/8
p=95/8
p=11 7/8
5)x+0,16=-1,24
x=-1,24-0,16
x=-1,4
6)-2-x=-0,8
-x=-0,8+2
-x=1,2
x=-1,2
7)|x-1|=3
1.x-1=-3
x=-3+1
x=-2
2.x-1=3
x=3+1
x=4
8)|x+3|=1
1.x+3=-1
x=-1-3
x=-4
2.x+3=1
x=1-3
x=-2